Evolution of Ciprofloxacin Resistance-Encoding Genetic Elements in Salmonella - Kaichao Chen (American Society for Microbiology, 2020)
ABSTRACT The incidence of ciprofloxacin resistance in Salmonella has increased dramatically in the past decade. To track the evolutionary trend of ciprofloxacin resistance-encoding genetic elements during this period, we surveyed the prevalence of Salmonella in food products in Shenzhen, China, during the period of 2012 to 2017 and performed whole-genome sequencing and genetic analysis of 566 ciprofloxacin-resistant clinical Salmonella strains collected during this survey. We observed that target gene mutations have become much less common, with single gyrA mutation currently detectable in Salmonella enterica serovar Typhimurium only. Multiple plasmid-mediated quinolone resistance (PMQR) genes located in the chromosome and plasmids are now frequently detectable in ciprofloxacin-resistant Salmonella strains of various serotypes. Among them, the qnrS1 gene was often harbored by multiple plasmids, with p10k-like plasmids being the most dominant. Importantly, p10k-like plasmids initially were not conjugative but became transmissible with the help of a helper plasmid. Ciprofloxacin resistance due to combined effect of carriage of the qnrS1 gene and other resistance mechanisms is common. In S. Typhimurium, carriage of qnrS1 is often associated with a single gyrA mutation; in other serotypes, combination of qnrS1 and other PMQR genes located in the chromosomal fragment or plasmid is observed. Another major mechanism of ciprofloxacin resistance, mainly observable in S. Derby, involves a chromosomal fragment harboring the qnrS2–aac(6′)lb-cr–oqxAB elements. Intriguingly, this chromosomal fragment, flanked by IS26, could form a circular intermediate and became transferrable. To conclude, the increase in the incidence of various PMQR mobile genetic elements and their interactions with other resistance mechanism contribute to a sharp increase in the prevalence of ciprofloxacin-resistant clinical Salmonella strains in recent years. IMPORTANCE Resistance of nontyphoidal Salmonella to fluoroquinolones such as ciprofloxacin is known to be mediated by target mutations. This study surveyed the prevalence of Salmonella strains recovered from 2,989 food products in Shenzhen, China, during the period 2012 to 2017 and characterized the genetic features of several PMQR gene-bearing plasmids and ciprofloxacin resistance-encoding DNA fragments. The emergence of such genetic elements has caused a shift in the genetic location of ciprofloxacin resistance determinants from the chromosomal mutations to various mobile genetic elements. The distribution of these PMQR plasmids showed that they exhibited high serotype specificity, except for the p10k-like plasmids, which can be widely detected and efficiently transmitted among Salmonella strains of various serotypes by fusing to a new conjugative helper plasmid. The sharp increase in the prevalence of ciprofloxacin resistance in recent years may cause a predisposition to the emergence of multidrug-resistant Salmonella strains and pose huge challenges to public health and infection control efforts.